Rancang Bangun Aplikasi Baca Buku Digital “UMKUPEDIA” Berbasis Website Menggunakan Framework Laravel - Fadilah, Riki Muhamad; Sofhian Fazrin Nasrulloh (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Dependence on third-party services causes problems because the management of digital books becomes inflexible and inefficient, which limits students' access to academic reading materials. This research aims to design, implement, and test a digital book reading application